"Mini" occipital seizures with accompanying ultra-slow waves (DC shift) on SEEG in a 14-year old child. (September 2019) - Gulati, Pratima; Kanaya, Kohei; Jain, Puneet; Weiss, Shelly; Otsubo, Hiroshi
Highlights: Brief occipital seizures may be under-diagnosed. Brief focal ultra-slow waves on intracranial EEG accompanying brief occipital seizures were noted. Ictal scalp EEG may be misleading for deep-seated epileptogenic lesions. Abstract: Occipital lobe epilepsies can present with complex or elementary visual hallucinations and oculomotor symptoms like contraversive tonic or clonic deviation of eyes and head. Brief occipital seizures can be difficult to diagnose. We report a child with occipital plus epilepsy who was investigated with stereo-EEG.